2016
DOI: 10.5812/modernc.11162
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Aqueous and Alcoholic Extracts of Barberry, Jujube, and Saffron Against Oxidative Stress in Streptozotocin-Induced Diabetic Rats

Abstract: Background: The use of herbal medicine has recently increased because of its effectiveness, limited side effects, and easy accessibility. In the present study, we investigated the antioxidant properties and diabetes treatment potential of 3 medicinal plants of barberry, saffron, and jujube.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…In this way, it directly scavenges superoxide-free radicals in the system, increases the expression of sirtuin 1, and decreases oxidative stress by reducing expression of nicotinamide and adenine dinucleotide phosphate oxidase which are critical sources for ROS production in cells. In line with the present research, the review study performed by Imenshahidi and co-workers showed that barberry and resveratrol might suppress TNF-α, IL-1, nitric oxide (NO), and MDA through the aforementioned mechanism (9,19,42,43). According to this mechanism, resveratrol and barberry increase SOD and TAC levels.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In this way, it directly scavenges superoxide-free radicals in the system, increases the expression of sirtuin 1, and decreases oxidative stress by reducing expression of nicotinamide and adenine dinucleotide phosphate oxidase which are critical sources for ROS production in cells. In line with the present research, the review study performed by Imenshahidi and co-workers showed that barberry and resveratrol might suppress TNF-α, IL-1, nitric oxide (NO), and MDA through the aforementioned mechanism (9,19,42,43). According to this mechanism, resveratrol and barberry increase SOD and TAC levels.…”
Section: Discussionsupporting
confidence: 88%
“…SOD and TAC were determined via the enzymatic colorimetric method with the microplate reader using enzymatic kits (ZV-TAC-A96) purchased from Zellbio Co., Germany. Additionally, MDA activity was determined via spectrophotometric analysis using thiobarbituric acid reactive substances (TBARS) method (19).…”
Section: Biochemical Markersmentioning
confidence: 99%